2021
DOI: 10.3758/s13423-021-01946-5
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive specialization for spatial memory does not improve route efficiency: Comparing the ability of Clark’s nutcrackers (Nucifraga columbiana) and pigeons (Columba livia) to solve traveling salesperson problems

Abstract: An important question in comparative cognition is whether animals are capable of planning ahead. Todd and Hills (Current Directions in Psychological Science, 29(3), 309-315, 2020) recently suggested that the ability to plan and choose internally may have scaffolded upon the cognitive mechanisms required by animals to search among patchy resources in their external environment. The traveling salesperson problem (TSP) is a spatial optimization problem in which a traveler is faced with the task of finding the b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…Similar research with pigeons has indicated that with novel configurations, performance is typically less efficient than the NN strategy, but that with training on a specific target configuration, performance improves to the point of exceeding NN (Baron et al, 2015;Gibson et al, 2012;Gibson et al, 2007). Recent evidence from birds also indicates that species with more robust spatial memories do not select more optimal routes, supporting the idea that the role of spatial memory in this task may be dissociable from a route planning or navigational component (Hales et al, 2021;Kelly et al, 2021).…”
mentioning
confidence: 70%
“…Similar research with pigeons has indicated that with novel configurations, performance is typically less efficient than the NN strategy, but that with training on a specific target configuration, performance improves to the point of exceeding NN (Baron et al, 2015;Gibson et al, 2012;Gibson et al, 2007). Recent evidence from birds also indicates that species with more robust spatial memories do not select more optimal routes, supporting the idea that the role of spatial memory in this task may be dissociable from a route planning or navigational component (Hales et al, 2021;Kelly et al, 2021).…”
mentioning
confidence: 70%
“…It has also analyzed the role of Confucian traditional culture in these relationships. Hypothesis 1 is accepted, showing that the heterogeneity of entrepreneurial team has positive influences on organizational resilience (Adaptive recovery ability and Integrated optimization ability) ( Kelly et al, 2021 ). Hypothesis 2 is also accepted, showing that cross-border search plays a mediating role between the heterogeneity of entrepreneurial team and adaptive recovery ability and integrated optimization ability of the organization.…”
Section: Discussionmentioning
confidence: 99%
“…Heterogeneous cooperation to meet challenges is called progress ( Ensley et al, 1998 ). According to the theory of heterogeneous advantage ( Lechler, 2001 ), within an organization, senior management teams with different backgrounds can view crisis events from different perspectives ( Yee et al, 2021 ), resulting in higher decision-making efficiency and stronger problem-solving ability ( Kelly et al, 2021 ). This multi-angle approach brings higher decision-making efficiency and stronger problem-solving ability to the organization ( Haryanto et al, 2021 ).…”
Section: Theoretical Basis and Hypothesismentioning
confidence: 99%